POWER RELATION AND SEVERITY OF OFFENSE IN THE STRATEGIES OF APOLOGIZING BY INDONESIAN EFL TEACHERS : A Case Study on Indonesian EFL Teachers at an English Course in Tasikmalaya - Harnani, - (2012)
This thesis is a descriptive case study concerning the strategies of apologizing. The study explores the apologizing strategy applied by Indonesian EFL teachers and finds out further whether power relation between the interlocutors, i.e. different and equal powers, and severity of the situations (Brown and Levinson, 1987; see also Al Fattah, 2010) affect the utterance and the applied strategy. This study employed a qualitative research design and one of the types of Discourse Completion Task (DCT): Discourse Role-Play Task (DRPT) was used as the main instrumentation to obtain the data. Other sources, such as observation, field notes, and informal interview were applied to strengthen the data. Subsequently, the data was analysed using Olshtain and Cohen's apologizing strategy (1983) as a guideline, consisting expression of apology (i.e. expression of regret, offer of apology, and request of forgiveness), explanation or account of the situation, acknowledgement of responsibility (accepting the blame, expressing self-deficiency, recognizing the other person as deserving apology, and expressing lack of intent), offer of repair, and promise of forbearance.The result of the study reveals that Indonesian teachers of English predominantly use the expression of apology, particularly expression of regret (see Al Fattah, 2010). Regarding power relation of the interlocutors, the study shows that Indonesian EFL learners apply different strategies for each hearer holding different power (see Al Fattah, 2010; Hou, 2006). The higher power status of the hearer, the more varied apology strategies and intensifiers applied. Meanwhile, severity of offense/ranking of imposition in this study also affects the length of apology expression. It is recommended that further research be constructed to highly consider other factors that may influence the strategy of apologizing, such as gender and cultural background. Therefore, the research may obtain a more thorough and comprehensive result.